Analisis Kualitatif Boraks Dan Formalin Terhadap Sifat Fisikokimia Ikan Petek Asin Di Pasar Celancang - Ikhwani; Hery Prambudi; Misika Alam; Vivi Alviansyah (Lembaga Pengembangan Kinerja Dosen, 2024)
Fish that have died rot very quickly compared to beef, fruit, or vegetables. This decay can be prevented by salting or what is commonly called salted fish. Aims to reduce the water content contained in fish meat, so that bacteria do not develop. In the processing of salted fish some producers add food ingredients. Like Borax and formalin which aims to preserve salted fish. Salted fish has many types, one of which is petek fish. This study aims to determine the presence of borax and formalin in the physicochemical properties of salted petek fish sold in Celancang market. The method in this study is descriptive qualitative with the method of examination using the flame test and curcumin paper on borax and using distillation with the addition of chromatopic acid on formalin. The samples in this study were salted petek fish sold in Celancang market as many as thirty samples. Based on the results of the research on the presence of borax test, there is no borax content in the salted petek fish sample and in formalin, as many as ten salted petek fish are positive for formalin sold in the Celancang market. From the organoleptic test results salted petek fish containing formalin is pure white in color different from the usual petek fish with a pungent aroma and hard texture but the taste remains the same salty.